Transparencia de la vejez y sociedad del espectáculo: pensar a partir de Simone de Beauvoir - Bernárdez Rodal, Asunción (Investigaciones Feministas (Feminist Research), 2009)
This paper inquires into Simone de Beauvoir’s writings on aging: their motivations, goals and thoughts, and howthe studies on this subject have political implications for women and feminism. Hier work has undoubtedlyinfluenced the artistic representations of the past decades in which many women artists have dared to contradictthe hegemonic representation of femininity, based on youth and beauty. This ascendancy is also present in women's associations and their fight against social exclusion and the marginalization of elderly women.
Keywords: Age; Feminism; Art; Women Artists; Performance